Malacofauna from soft bottoms in the Cerro Gordo marine cave (Alboran Sea): biodiversity and spatial distribution - PINO DE LA TORRE, LIDIA; NAVARRO-BARRANCO, CARLOS; GOFAS, SERGE (Mediterranean Marine Science, 2020)
A study has been carried out for the first time of the molluscan fauna of the Cerro Gordo submarine cave in the Spanish part of the Alboran Sea. The depth of the cave bottom ranges from 16 m at its entrance, to sea level at its innermost section. Replicate soft-bottom samples were collected from three different stations along the horizontal gradient of the cave. Additional samples were collected on photophilous hard bottoms next to the cave entrance in order to assess the origin of cave bioclasts. The cave sediments contained 158 species of molluscs (23 collected alive and 155 recorded as shells), more than in Mediterranean cave sediments elsewhere. Species richness and abundance of molluscs decreased from the outermost to the innermost part of the cave. No cave-exclusive species were found, possibly due to the scarcity of caves in the Alboran Sea, but many of the recorded species are known from other Mediterranean caves. The lack of adult individuals for most of the living species inside the cave, suggests that these do not constitute self-maintaining populations. Finally, our results suggest that bioclasts found in the sediment do not derive from the outside of the cave nor from the sediment itself, but mostly from the communities inhabiting the walls and ceiling of the cave.